Building Fire Preparedness Among Elementary Students Through School-Based Evacuation Drills at SDN 004 Teritip, Balikpapan - Rafi Achmad Taqi; Safri Gunawan; Bayu Aquaria Januarta; Nabil Keiza Ibrahimovic; Mursalam Mursalam; Nurul Awaliyah; Retnowaty Retnowaty; Ari Musdolifah; Nurliani Maulida; Rika Istianingrum (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
Fires are among the most common emergencies that may occur in school environments and pose significant risks to students and school personnel if appropriate preparedness measures are not in place. Fire safety education and evacuation simulations play an important role in developing students' knowledge, emergency response skills, and safety awareness from an early age. This community service program aimed to improve the fire safety knowledge and emergency preparedness of sixth-grade students at SDN 004 Teritip, East Balikpapan, through interactive education and practical evacuation simulations. The program involved 45 students and consisted of fire safety education, question-and-answer sessions, a fire evacuation simulation, a four-question quiz, and an educational game. Data were collected through direct observation, quiz results, and photographic documentation and analyzed descriptively. The findings indicated that students actively participated in all activities and demonstrated a better understanding of fire hazards, evacuation procedures, and the function of assembly points. During the simulation, students were able to follow evacuation instructions in an orderly manner and showed increased confidence in responding to emergency situations. These results suggest that integrating interactive education with hands-on evacuation simulations is an effective approach to strengthening fire safety awareness and emergency preparedness among elementary school students. Therefore, regular implementation of fire safety education and evacuation drills is recommended to foster a sustainable culture of safety in schools..